The Role of The Bandung Regency Government in Disaster Response to Covid – 19 - Dedy Suhendi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
As it is known that the Indonesian nation is very vulnerable to disasters. Almost every year, maybe even every year, the Indonesian people always face disasters, especially floods during the rainy season and or drought during the dry season.At this time the Indonesian people and several nations in the world are focusing on tackling the spread of the corona virus (covid - 19) disaster and the challenges they are facing are increasingly increasing. The government needs a comprehensive and integrated management planning strategy, which can be implemented by all elements of government, both central and regional governments and the community in a coordinated manner.The important role of local government in handling Covid - 19 is the most important. All stakeholders, both at the central and regional levels, must increase their hard work in a more coordinated and integrated manner so that the impact caused by Covid - 19 can be minimized and even an antidote can be found.Based on this, researchers are encouraged to try to describe and explain the role of the Bandung district government which is considered relatively successful in tackling the disaster caused by the Covid - 19 pandemic.